1997
DOI: 10.1017/s0031182096008098
|View full text |Cite
|
Sign up to set email alerts
|

Non-specific binding of mouse IgG1 to Heligmosomoides polygyrus: parasite homogenate can affinity purify mouse monoclonal antibodies

Abstract: A characteristic feature of infections with the nematode parasite of mice Heligmosomoides polygyrus, is a marked IgG1 hypergammaglobulinaemia. A possible source for this immunoglobulin has recently been demonstrated, through evidence that H. polygyrus adult worm homogenate (AWH) can induce the in vitro production of non-specific IgG1 from mouse lymphocytes. To determine the interactions between this immunoglobulin and the parasite, the ability of IgG1 to bind to AWH of H. polygyrus was investigated. Protein (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…We had previously shown that MAb 13B3 binds to proteins found in the adult worm homogenate (AWH) of H. polygyrus (17). We extended these observations to show that the MAb also was able to bind to a combination of proteins found in the E/S of both adult and L4 stages of the parasite (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We had previously shown that MAb 13B3 binds to proteins found in the adult worm homogenate (AWH) of H. polygyrus (17). We extended these observations to show that the MAb also was able to bind to a combination of proteins found in the E/S of both adult and L4 stages of the parasite (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…(13). The MAb had been initially produced against adult worm homogenate (17), and it was therefore of interest to note that one MAb, called 13B3, was able to bind to a proteins found in both adult and L4 E/S (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations